2015
DOI: 10.1038/ncomms7363
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate DNA methylation is a conserved signature of genome regulation

Abstract: The role of intermediate methylation states in DNA is unclear. Here, to comprehensively identify regions of intermediate methylation and their quantitative relationship with gene activity, we apply integrative and comparative epigenomics to 25 human primary cell and tissue samples. We report 18,452 intermediate methylation regions located near 36% of genes and enriched at enhancers, exons, and DNase I hypersensitivity sites. Intermediate methylation regions average 57% methylation, are predominantly allele-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 46 publications
(62 reference statements)
8
78
2
Order By: Relevance
“…However, the Pcdh-associated CpG islands do not show uniparental methylation patterns, in contrast to the observed pattern at the DMRs of IGs [37]. We show that promoter regions of PCDH variable exons have hemimethylated CpGs in multiple human tissues; three allele-independent methylation regions have been recently reported in PCDH-α, in adult human blood, and breast samples [31]. Pcdh non-imprinted monoallelic and random isoform expression has been previously demonstrated in mice; given the evolutionarily conserved organization of the PCDH clusters, this unique type of monoallelic expression might be present in human tissues as well, although this assumption needs validation.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…However, the Pcdh-associated CpG islands do not show uniparental methylation patterns, in contrast to the observed pattern at the DMRs of IGs [37]. We show that promoter regions of PCDH variable exons have hemimethylated CpGs in multiple human tissues; three allele-independent methylation regions have been recently reported in PCDH-α, in adult human blood, and breast samples [31]. Pcdh non-imprinted monoallelic and random isoform expression has been previously demonstrated in mice; given the evolutionarily conserved organization of the PCDH clusters, this unique type of monoallelic expression might be present in human tissues as well, although this assumption needs validation.…”
Section: Discussioncontrasting
confidence: 63%
“…The putative imprinted gene SYCE1 (synaptonemal complex central element protein 1) had the ASE demonstrated in multiple human tissues [20]. Four hypomethylated CpG sites were found in the PTCHD3 (patched domain containing 3) promoter region in patients with Beckwith-Wiedemann syndrome and multilocus hypomethylation [15]; moreover, an allele-specific methylation region in PTCHD3 exon 1 has been recently reported in human breast and blood samples [31], reinforcing the hypothesis of imprinting. Apart from ZNF331, the other genes have not yet been validated.…”
Section: Discussionmentioning
confidence: 60%
“…Prior studies have also suggested that intermediate levels of methylation are frequently found around transcription factor (TF) binding sites 13,29,30 . To compare these local events with the global patterns described above, we re-examined our bulk and arrested ESC datasets and utilized previously determined TF binding sites based on chromatin immunoprecipitation followed by sequencing (ChIP-seq) experiments in ESCs as well as their differentiated derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…While the methylation status of individual CpG sites is generally consistent among alleles, resulting in methylated or unmethylated CpG sites in all alleles, there are certain regions that show heterogeneity in methylation status among alleles. The methylation heterogeneity (intermediate methylation 1 or partially methylated domain 2 ) is reported in primordial germ cells under epigenetic reprogramming, 3 sperms, 4 embryonic stem cells, 5 induced pluripotent stem cells, 6 placental cells, 2 and other somatic cells under normal and disease conditions. [7][8][9] These regions are highly gene enriched and often interact with other epigenetic markers such as histone modifications.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] These regions are highly gene enriched and often interact with other epigenetic markers such as histone modifications. 1 In embryonic stem cells, allelic heterogeneity is involved in maintaining the bimodal states of gene expression. 5 Furthermore, allelic heterogeneity is frequently found in various types of cancer cells, and the possible relationship with aberrant gene expression in cancer cells is of particular interest.…”
Section: Introductionmentioning
confidence: 99%